2003
DOI: 10.1583/1545-1550(2003)010<0978:patsss>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Adhesion to Simulated Stented Surfaces

Abstract: Additional knowledge of the role of mechanical factors in stent restenosis will aid in designing stents that minimize intimal hyperplasia and restenosis. The results of this study demonstrate the importance of stent design-mediated blood flow patterns, with smaller strut spacings minimizing platelet adhesion per unit strut area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…20 The observation in this study that platelet deposition is still increasing between the intermediate struts, compared with upstream, may confirm this previous observation. We have also identified distinct flow regions within struts, such as recirculation, reattachment, and separation, and correlated these flow regions with localized platelet deposition in a highly resolved scale.…”
Section: Figure 8 (A) Average Normalized Platelet Deposition Betweensupporting
confidence: 89%
See 4 more Smart Citations
“…20 The observation in this study that platelet deposition is still increasing between the intermediate struts, compared with upstream, may confirm this previous observation. We have also identified distinct flow regions within struts, such as recirculation, reattachment, and separation, and correlated these flow regions with localized platelet deposition in a highly resolved scale.…”
Section: Figure 8 (A) Average Normalized Platelet Deposition Betweensupporting
confidence: 89%
“…In our previous study, platelet deposition on the wall in a 2D stented region was shown to vary significantly with different stent strut spacings. 20 The stent model with the closest spacing (L/H = 2.5) produced the lowest amount of platelet deposition both between stents and on the struts as compared to the intermediate (L/H = 4.0) and widest spacing (L/H = 7.0) models. However, the method used to trace platelets, radioactive labeling, did not provide us with direct observation of the attachment of platelets between the struts, or the spatial distribution of platelets between the struts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations